Selection cycles of half-sib families for the maize variety BR 5011 Sertanejo - Carvalho, Hélio Wilson Lemos de; Souza, Evanildes Menezes de (Pesquisa Agropecuaria Brasileira, 2010)
The objective of this work was to estimate the genetic parameters of the maize variety BR 5011 Sertanejo, in order to evaluate the behavior of the genetic variability along successive selection cycles. Seventeen betweenand within-half-sib family selection cycles and three stratified mass selections were carried out for this maize variety, between 1985 and 2005. In the three first selection cycles of between- and within-half-sib families, families were evaluated using a 10x10 lattice, whereas for the reminder of the cycles, a 14x14 lattice was employed. The assays were carried out in the municipalities of Gararu, Propriá, Poço Verde, Neópolis, Lagarto and Nossa Senhora das Dores, in Sergipe State, and at Cruz das Almas, Bahia State. The plots were composed by 5 m rows spaced at 0.8 m, and within-row spacing of 0.4 m. The recombination of the selected families was made within the same agricultural year, as to get one cycle per year. The maize variety BR 5011 Sertanejo presented a high yield potential and a wide genetic variability. The highly significant family x site interaction highlighted the importance of evaluating productivity across multiple sites, in order to improve the efficiency of selection process and get more reliable estimates of variance components.